Skills and talent of immigrants: a comparison between the European Union and the United States - Giovanni Peri (University of California, Department of Economics, 2005)
The nineties has been a period of increasing migratory flows from less developed countries to industrialized nations. It is instructive to compare the two largest economies in the world, the European Union and the United States, in terms of the magnitude, trends and composition of their migratory inflows. While the two economies are similar in terms of size and level of development, the European Union still lags behind in its ability to attract immigrants and in the degree of internal mobility of its citizens. Moreover we document a general feature that became more prominent during the nineties. While both economies attracted less educated workers (primary school graduates) as well as highly educated workers (college graduates) from less developed countries, the United States have been able to attract "talent",( i.e. the best among the skilled workers) from all over the world at a rate unmatched by the European Union. In fact the US attracted a large number of talents from the European Union itself during the nineties. This "brain drain" (probably driven by the large economic reward granted by the American economy to scientific, technological and professional talent) is worrisome for the European Union. Its ability to keep pace with the economic growth of the United States depends, in fact, on its ability to compete in the scientific and technological fields.
Keywords: 330